Health of the Nation Outcome Scales for Infants field trial: concurrent validity. Issue 4 (12th July 2021) - Brann, Peter; Culjak, Gordana; Kowalenko, Nick; Dickson, Rosemary; Coombs, Tim; Burgess, Philip; Williams, Anne Sved; Hoehn, Elisabeth; Hoyland, Margaret
Abstract : Background: A review of Australian mental health services identified a gap in routine outcome measures addressing social, emotional and behavioural domains for pre-schoolers and infants. A Child and Adolescent Mental Health Information Development Expert Advisory Panel working group developed the Health of the Nation Outcome Scales for Infants (HoNOSI), a clinician-reported routine outcome measure for infants 0–47 months. Prior face validity testing showed that the HoNOSI was considered useful in measuring mental health outcomes. Aims: To examine the concurrent validity of the HoNOSI. Method: Mental health clinicians providing assessment and treatment to infants in routine clinical practice participated in the study. The mental health status of 108 infants were rated by a minimum of 26 clinicians with the HoNOSI, the Parent-Infant Relationship Global Assessment Scale (PIR-GAS) and measures of symptom severity and distress. Results: The HoNOSI was statistically significantly correlated with the PIR–;GAS, rs = −0.73; Clinical Worry, rs = 0.77; and Severity Judgement ratings, rs = 0.85; P < 0.001. A good level of internal consistency was found. Using the COsensus-based Standards for the selection of health Measurement INstruments (COSMIN) criteria for judging instrument acceptability, the HoNOSI meets the standard for both concurrent validity and internal consistency. Conclusions: There has been a clear need for a routine outcome measure for use with infants. This study provides positive evidence of aspects of validity. These findings, along with those from the prior face validity study, support a controlled release of the HoNOSI accompanied by further research and development.